Millenium development goals/UN and sustainable development goals/UN as instruments for realising sustainable development concept in the global economy - Zofia Wysokińska (Comparative Economic Research. Central and Eastern Europe, 2017)
This article presents the results of analysis and evaluation of the main effects of the implementation of the eight UN Millennium Development Goals, in force until 2015, and to demonstrate differences between and prospects for implementation of the new 2030 Agenda for Sustainable Development, covering 17 Sustainable Development Goals (SDGs) established by the international community for the next 15 years. The article also presents the contribution of the European Union as a key global donor of development aid for developing countries, especially for the least developed countries (LDCs), as well as plans for Poland's implementation of the Post-2015 Agenda SDGs.
Keywords: 330; Millennium Development Goals; Sustainable Development Goals; European Union; Poland